IoT-Based Driver Health Monitoring System with Location Based Service Feature for Fast Treatment at Nearest Health Facilities - Jaya, Dery Yuswanto (International Journal of Health Engineering and Technology, 2025)
This research aims to develop and test an Internet of Things (IoT)-based driver health monitoring system with Location Based Service (LBS) features for quick response to the nearest health facility. The system uses health sensors (heart rate, body temperature, SpO2, and fatigue), GPS module, and Wi-Fi/GSM-based communication to monitor the driver's condition in real-time. The research method includes system design, sensor testing, field testing with 25 drivers, and system performance analysis. The results show that the health sensor has an accuracy above 90%, with detection of critical conditions within 3-5 seconds and sending emergency notifications within 10 seconds. The LBS feature successfully provided health facility recommendations with 98% accuracy. Field tests detected several cases of critical conditions and proved the effectiveness of the system in real conditions. Ninety percent of participants expressed satisfaction with the system. The research conclusion confirms that the system can improve driver safety, reduce the risk of accidents due to health problems, and has the potential for wide application in the transportation and logistics sectors. However, there are limitations such as dependence on the internet and the accuracy of fatigue sensors that need to be improved in future research.